Case mix adjusted variation in cesarean section rate in Sweden. (30th March 2017) - Mesterton, Johan; Ladfors, Lars; Ekenberg Abreu, Anna; Lindgren, Peter; Saltvedt, Sissel; Weichselbraun, Marianne; Amer‐Wåhlin, Isis
Abstract: Introduction: Cesarean section (CS) rate is a well‐established indicator of performance in maternity care and is also related to resource use. Case mix adjustment of CS rates when performing comparisons between hospitals is important. The objective of this study was to estimate case mix adjusted variation in CS rate between hospitals in Sweden. Material and methods: In total, 139 756 deliveries in 2011 and 2012 were identified in administrative systems in seven regions covering 67% of all deliveries in Sweden. Data were linked to the Medical birth register and population data. Twenty‐three different sociodemographic and clinical characteristics were used for adjustment. Analyses were performed for the entire study population as well as for two subgroups. Logistic regression was used to analyze differences between hospitals. Results: The overall CS rate was 16.9% (hospital minimum–maximum 12.1–22.6%). Significant variations in CS rate between hospitals were observed after case mix adjustment: hospital odds ratios for CS varied from 0.62 (95% CI 0.53–0.73) to 1.45 (95% CI 1.37–1.52). In nulliparous, cephalic, full‐term, singletons the overall CS rate was 14.3% (hospital minimum–maximum: 9.0–19.0%), whereas it was 4.7% for multiparous, cephalic, full‐term, singletons with no previous CS (hospital minimum–maximum: 3.2–6.7%). In both subgroups significant variations were observed in case mix adjusted CS rates. Conclusions: Significant differences in CS rate between Swedish hospitals were found after adjusting for differences in case mix. This indicates a potential for fewer interventions and lower resource use in Swedish childbirth care. Best practice sharing and continuous monitoring are important tools for improving childbirth care.